Exploratory study on autoantibodies to arginine-rich human peptides mimicking Epstein-Barr virus in women with post-COVID and myalgic encephalomyelitis/chronic fatigue syndrome - Hoheisel, Friederike; Fleischer, Kathrin Maria; Rubarth, Kerstin; Sepúlveda, Nuno; Bauer, Sandra; Konietschke, Frank; Kedor Peters, Claudia; Stein, Annika Elisa; Wittke, Kirsten; Seifert, Martina; Bellmann-Strobl, Judith; Mautner, Josef; et al. (Frontiers in Immunology, 2025)
IntroductionEpstein-Barr virus (EBV) infection is a well-established trigger and risk factor for both myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and post-COVID syndrome (PCS). In previous studies, we identified elevated IgG responses to arginine-rich (poly-R) sequences within the EBV nuclear antigens EBNA4 and EBNA6 in post-infectious ME/CFS (piME/CFS). Building on these findings, this exploratory study examines IgG reactivity to poly-R-containing EBV-derived peptides and homologous human peptides in women with PCS and ME/CFS.MethodsIgG reactivity to poly-R containing peptides derived from EBNA4 and EBNA6, and homologous human 15-mer peptides and the corresponding full-length proteins, was assessed using a cytometric bead array (CBA) and a multiplex dot-blot assay. Serum samples were analyzed from 45 female PCS patients diagnosed according to WHO criteria, including 26 who also met the Canadian Consensus criteria for ME/CFS (pcME/CFS), 36 female patients with non-COVID post-infectious ME/CFS (piME/CFS), and 34 female healthy controls (HC).ResultsAutoantibodies targeting poly-R peptide sequences of the neuronal antigen SRRM3, the ion channel SLC24A3, TGF-β signaling regulator TSPLY2, and the angiogenesis-related protein TSPYL5, as well as full-length α-adrenergic receptor (ADRA) proteins, were more frequently detected in patient groups. Several of these autoantibodies showed positive correlations with core symptoms, including autonomic dysfunction, fatigue, cognitive impairment, and pain.ConclusionThis exploratory study identify autoantibodies directed against EBV mimicking arginine-rich sequences in human proteins, suggesting a potential role for molecular mimicry in the pathogenesis of PCS and ME/CFS.